The Relationship Between Antenatal Care Attendance Compliance and Preeclampsia in Pregnant Women in the Working Area of the Majasem Community Health Center in Cirebon City - Battya, Annesya Atma (INDOGENIUS, 2025)
Background & Objective: Antenatal care is a health service provided to pregnant women by health workers, involving the monitoring of the physical and psychological health of pregnant women and the growth and development of the fetus in accordance with established procedures and schedules. Regular ANC can detect abnormalities early, particularly those related to preeclampsia, thereby preventing mild preeclampsia, severe preeclampsia, and eclampsia and enabling appropriate treatment. Preeclampsia is one of the conditions experienced and caused during pregnancy. This study aims to determine the relationship between compliance with antenatal care visits and preeclampsia in pregnant women in the Majasem Public Health Center (Puskesmas) area of Cirebon City. Method: This study is a quantitative descriptive correlation study with a retrospective approach. The sample was selected using total sampling, with a total of 33 respondents. The instrument used was a data summary sheet. Data analysis was performed using the chi-square test. The study was conducted in the Majasem Public Health Center area in Cirebon City from May to June 2022. Result: The research results showed that most respondents did not comply with antenatal care visits according to the specified distribution or requirements, with 12 (26.4%) compliant and 21 (63.6%) non-compliant, and 26 (78.8%) with mild preeclampsia and 7 (21.2%) with severe preeclampsia. The chi-square test yielded a p-value of 0.687 > α = 0.05, so H_a was accepted, meaning there was no association between compliance with antenatal care visits and preeclampsia among pregnant women in the service area of the Majasem Health Center in Cirebon City. Conclusion: There is no association between compliance with antenatal care visits and preeclampsia among pregnant women in the service area of the Majasem Health Center in Cirebon City.